2003
DOI: 10.1161/01.hyp.0000073843.56046.45
|View full text |Cite
|
Sign up to set email alerts
|

Aging Increases Aortic MMP-2 Activity and Angiotensin II in Nonhuman Primates

Abstract: Abstract-To seek evidence that the nonhuman primate arterial wall, as it ages in the absence of atherosclerosis, exhibits alterations in pathways that are involved in the pathogenesis of experimental atherosclerosis, we assessed aortic matrix metalloproteinase-2 (MMP-2) and its regulators, ie, membrane type-1 of matrix metalloproteinase (MT1-MMP) and tissue inhibitor of matrix metalloproteinase-2 (TIMP-2), and the expression of angiotensin II (Ang II), angiotensinconverting enzyme (ACE), and chymase in young (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
241
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 215 publications
(250 citation statements)
references
References 50 publications
(58 reference statements)
7
241
0
2
Order By: Relevance
“…We evaluated the regulating effects of testosterone on MMP-2 activity, a critical downstream molecule of angiotensin II system (Wang et al 2003). Both the expression level and activity of MMP-2 were dramatically elevated in the central arterial wall with advancing age and played pivotal roles in facilitating age-associated ECM remodeling (Jiang et al 2012;).…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated the regulating effects of testosterone on MMP-2 activity, a critical downstream molecule of angiotensin II system (Wang et al 2003). Both the expression level and activity of MMP-2 were dramatically elevated in the central arterial wall with advancing age and played pivotal roles in facilitating age-associated ECM remodeling (Jiang et al 2012;).…”
Section: Discussionmentioning
confidence: 99%
“…Salient features of the age-associated changes in the media include the deposition of extracellular matrix proteins such as fibronectin and type-2 matrix metalloprotease (MMP- 2), 52,58,66 which promotes matrix protein degradation and facilitates VSMC migration. 67 Aortic medial VSMCs from older rats are larger in size and fewer in number than those in the aorta from young adult rats.…”
Section: Aging Of the Arterial Mediamentioning
confidence: 99%
“…The age‐associated increase in activation of MMP2 is mediated via an imbalance of its activator, membrane type 1 MMPs (MT1‐MMP), and its inhibitor, TIMP2 8, 18. Immunostaining analysis demonstrated that the expression of aortic membrane type 1 MMP (brown) and TIMP2 (brown) was substantially increased in old versus young AL, but this effect was markedly reduced in CR rats (Figure 8A through 8C).…”
Section: Resultsmentioning
confidence: 99%
“…PDGF‐BB is not only a potent mitogen, but also a strong chemoattractant of VSMCs, creating a permissive tissue microenvironment for VSMC migration and invasion, promoting formation of a thickened intima in vivo 1, 2, 3, 8, 41, 42. Prior findings indicate that PDGF‐BB treatment induces invasion and migration of old VSMCs in vitro 8, 9. The capacity of VSMC to repopulate a damaged area in vitro, a model for the cellular process of thickening intimal or neointimal formation, is markedly increased after PDGF‐BB treatment 43, 44.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation